A retrospective evaluation of the presentation, prognostic factors and outcomes of neuroblastoma in Ugandan children. (3rd April 2023) - Nanyanga, Irene; Kwikiriza, Gideon Kurigamba; Atwiine, Barnabas; Namazzi, Ruth; Musiime, Victor; Kambugu, Joyce Balagadde; van Heerden, Jaques
Abstract: Neuroblastoma (NB) is the most common extracranial solid tumor of childhood. The complete burden and outcomes in Uganda are unknown. The study was a multicenter retrospective chart review of children aged between 0 to 15 years diagnosed with NB from 2010 to 2020. Demographic, clinical and tumor-related characteristics were extracted for analysis. Kaplan-Meier survival curves and Cox regression models were used to determine the one-year overall survival (OS) and identify prognostic factors. Seventy-five patients were evaluated, with a median age at diagnosis of 48 months (IQR 26-108 months). Fever (74.7%), weight loss (74.7%), high blood pressure (70.3%) and abdominal swelling/mass (65.3%) were the most common features at diagnosis. Suprarenal tumors (52%) and stage 4 disease (70.7%) were also common. The one-year OS was 60.0% (95%CI 56.8%; 64.3%) with a median survival time of 12.6 months (95% CI: 8.1; 20.8). The one-year OS for non-metastatic and metastatic disease was 67.3% and 42.6% ( p = 0.11) respectively. Leukocytosis ( p < 0.001) at diagnosis was of prognostic significance while clinical remission after induction chemotherapy ( p < 0.001) provided survival advantages. Children who received maintenance chemotherapy had a longer median survival time of 38.5 months (range 10.8–69.5). Age ( p = 0.001), lung metastasis ( p < 0.001), and leukocytosis ( p < 0.001) remained significant on multivariate analysis. In this Ugandan study, leukocytosis was a clinical predictor of prognosis, metastatic disease had management challenges and maintenance chemotherapy prolonged the survival time but not OS. LEARNING POINTS: Ugandan children diagnosed with neuroblastoma present with advanced disease. Surgery and radiotherapy are under-utilized in the management of neuroblastoma, but have prognostic value in neuroblastoma outcomes. Children under the age of 12 months are under-diagnosed in Uganda, but those that do present for treatment fare poorer than older age groups. The overall survival is poor but the survival time can be increased with maintenance chemotherapy.